2014
DOI: 10.1101/lm.035501.114
|View full text |Cite
|
Sign up to set email alerts
|

A unifying model of the role of the infralimbic cortex in extinction and habits

Abstract: The infralimbic prefrontal cortex (IL) has been shown to be critical for the regulation of flexible behavior, but its precise function remains unclear. This region has been shown to be critical for the acquisition, consolidation, and expression of extinction learning, leading many to hypothesize that IL suppresses behavior as part of a "stop" network. However, this framework is at odds with IL function in habitual behavior in which the IL has been shown to be required for the expression and acquisition of ongo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 94 publications
(112 reference statements)
7
58
1
Order By: Relevance
“…Extensive research has focused on elucidating the circuitry underlying habit formation and expression. While it is generally thought that subregions of the prefrontal cortex mediate cognitive control of actions, the infralimbic prefrontal cortex (IfL-C) appears to sub-serve habitual, stimulus-driven reward seeking (Killcross and Coutureau 2003; Coutureau and Killcross 2003; Smith et al, 2012; Smith and Graybiel 2013; Barker et al, 2014). The IfL-C is critical for both the acquisition (Killcross and Coutureau, 2003) and expression (Coutureau and Killcross, 2003; Smith et al, 2012) of habitual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has focused on elucidating the circuitry underlying habit formation and expression. While it is generally thought that subregions of the prefrontal cortex mediate cognitive control of actions, the infralimbic prefrontal cortex (IfL-C) appears to sub-serve habitual, stimulus-driven reward seeking (Killcross and Coutureau 2003; Coutureau and Killcross 2003; Smith et al, 2012; Smith and Graybiel 2013; Barker et al, 2014). The IfL-C is critical for both the acquisition (Killcross and Coutureau, 2003) and expression (Coutureau and Killcross, 2003; Smith et al, 2012) of habitual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…While dorsal regions of mPFC-anterior cingulate cortex (ACC) and prelimbic cortex (plPFC)-are not required for PIT (Cardinal et al 2003;Corbit and Balleine 2003), a role for the more ventral infralimbic cortex (ilPFC) has not been investigated. IlPFC regulates flexible reward seeking and may facilitate cuecontrolled behavior (Barker et al 2014). IlPFC sends a dense glutamatergic projection to NAcS, a structure that is itself necessary for specific PIT (Corbit and Balleine 2011), and this projection is known to inhibit inappropriate reward seeking (Vertes 2004;Peters et al 2008Peters et al , 2009Bossert et al 2012).…”
mentioning
confidence: 99%
“…It is also known to mediate habitual behavior, as indexed by persistent responding even after reward contingencies or values have been disrupted (Killcross and Coutureau 2003). Thus, the ilPFC can be thought of as actively suppressing action-outcome contingencies in both extinction and habitual behaviors (Barker et al 2014). In the same way ilPFC suppresses inappropriate goal-directed behavior in extinction and habit paradigms, it may also be suppressing "inappropriate" responding in PIT, i.e., responding during pre-CS and different-CS intervals.…”
mentioning
confidence: 99%
“…Further, it is well--known that activity--dependent neural changes reflect forms of associative (or Hebbian) learning, whereby interconnected neurons that are active 15 For e.g., see : Wolters et al, 2003;Huber et al 2004;Floyer--Lea et al 2006;Roy et al 2007;Albert et al 2009;Feldman 2009;2012;Wang 2010;Mrachacz--Kersting 2012;Orban de Xivry et al 2013;Koch et al 2013;Hammerbeck et al 2014;Barker et al 2014;McNickle & Carson 2015;Chao et al 2015. Also, it has, for instance, been observed that, as a behavior is repeated, certain motor--related neural activities become more probable under certain conditions (e.g., Costa 2007;Wickens et al 2007;Graybiel 2008;Verstynen & Sabes 2011;Hikosaka et al 2013;Kim et al 2015;Anderson 2016). together are subsequently more likely to be active together under certain conditions, and vice versa (e.g., Hebb 1949;Klaes et al 2012).…”
Section: The Wild Coincidence Objection: An Empirical Objection Withomentioning
confidence: 99%